Organizing supply chain processes for sustainable innovation in the agri-food industry - Cagliano, Raffaella; Caniato, Federico F. A.; Worley, Christopher G.; Shani, Abraham B.; Mohrman, Susan Albers; Emerald eBooks (Bingley, U.K. : Emerald, 2016)
The sustainability of agri-food supply chains is particularly relevant for global sustainable development. Many existing food production systems do more harm than good. They compromise the natural rhythms of the Earth, introduce toxins, and therefore sacrifice future capability for current demands the opposite of sustainable development norms. The existing system is also unbalanced with respect to its capacity to produce, the amount of waste it generates, the number of people who suffer from hunger, and the nutritional value it provides. Most of the current supply chains have been developed within the classic economic paradigm, where scale and leverage drive choices towards more profitable models. As a consequence, finding new ways to produce, distribute and consume food is a morale, financial, and environmental necessity. Sustainable development and triple bottom line perspectives provide the logic for questioning this paradigm. This book presents and discusses nine cases of organizational innovation in food supply chain, covering different phases of food production, facing different challenges, and proposing different solutions to the challenge of sustainable food development.
The challenge of sustainable innovation in agri-food supply chains / Raffaella Cagliano, Christopher Worley, Federico Caniato -- Alcass: innovation for sustainable supply chains for traditional and new products / Vero<U+0301>nica Leo<U+0301>n-Bravo, Federico Caniato, Antonella Moretto, Raffaella Cagliano -- Supporting sustainability through developing a learning network among traditional food producers: applications of action learning / Paul Coughlan, David Coghlan, Denise O'Leary, Clare Rigg, Doireann Barrett -- Building social capital into the disrupted green coffee supply chain: Illy's journey to quality and sustainability / Annachiara Longoni, Davide Luzzini -- The evolution of Barilla's durum wheat supply chain contracts for triple bottom line benefits / Marco Formentini, ManMohan Sodhi, Christopher Tang -- Minimizing food waste at Google: creating production innovation and purchasing practices / Madeleine Pullman, Kristen Rainey -- Surplus food redistribution for social purposes: the case of Coop Lombardia / Sedef Sert, Paola Garrone, Marco Melacini, Alessandro Perego -- Packaging's role in sustainability: reusable plastic containers in the agricultural-food supply chains / Jay Singh, Abraham Shani, Hillary Femal, Ahmed Deif -- Origin green: when your brand is your supply chain / Mary Shelman, Damien McLoughlin, Mark Pagell -- The emergence of a local foods network in Northeast Ohio / Susan Mohrman, Sally Parker, Lorelei Palacpac, Cameron Wilk -- Inclusive innovation and the role of partnerships: the case of Semi di Liberta<U+0300> / Francesca Mapelli, Marika Arena, Paolo Strano -- A pathway towards truly sustainable food supply chains: balancing motivation, strategy, and impact / Raffaella Cagliano, Federico Caniato, Christopher Worley.
Includes bibliographical references.
Keywords: Business & Economics -- Organizational Behavior; Organizational theory & behaviour; Business logistics; Organizational sociology; Sustainable development; Electronic books